Plant and microbial responses to nitrogen and phosphorus addition across an elevational gradient in subarctic tundra - Sundqvist, Maja K.; Zhanfeng Liu; Giesler, Reiner; Wardle, David A. (Figshare, 2016)
Temperature and nutrients are major limiting factors in subarctic tundra. Experimental manipulation of nutrient availability along elevational gradients (and thus temperature) can improve our understanding of ecological responses to climate change. However, no study to date has explored impacts of nutrient addition along a tundra elevational gradient, or across contrasting vegetation types along any elevational gradient. We set up a full factorial nitrogen (N) and phosphorus (P) fertilization experiment in each of two vegetation types (heath and meadow) at 500 m, 800 m, and 1000 m elevation in northern Swedish tundra. We predicted that plant and microbial communities in heath or at lower elevations would be more responsive to N addition while communities in meadow or at higher elevations would be more responsive to P addition, and that fertilizer effects would vary more with elevation for the heath than for the meadow. Although our results provided little support for these predictions, the relationship between nutrient limitation and elevation differed between vegetation types. Most plant and microbial properties were responsive to N and/or P fertilization, but responses often varied with elevation and/or vegetation type. For instance, vegetation density significantly increased with N + P fertilization relative to the other fertilizer treatments, and this increase was greatest at the lowest elevation for the heath but at the highest elevation for the meadow. Arbuscular mycorrhizae decreased with P fertilization at 500 m for the meadow, but with all fertilizer treatments in both vegetation types at 800 m. Fungal to bacterial ratios were enhanced by N + P fertilization for the two highest elevations in the meadow only. Additionally, microbial responses to fertilization were primarily direct rather than indirect via plant responses, pointing to a decoupled response of plant and microbial communities to nutrient addition and elevation. Because our study shows how two community types differ in their responses to fertilization and elevation, and because the temperature range across this gradient is ∼3°C, our study is informative about how nutrient limitation in tundra may be influenced by temperature shifts that are comparable to those expected under climate change during this century.